Impaired renal endothelial nitric oxide synthase and reticulocyte production as modulators of hypertension induced by rHuEPO in the rat - Ribeiro, Sandra (2016)
Our aim was to study the effect of a broad range of recombinant human erythropoietin (rHuEPO) doses on hematological and biochemical parameters, blood pressure (BP), renal function and damage in the rat, focusing on endothelial nitric oxide synthase (eNOS) and hypoxia-inducible factors (HIFs). Male Wistar rats were divided in 5 groups receiving different doses of rHuEPO (100, 200, 400 and 600IU/kg body weight (BW)/week) and saline solution (control), during 3weeks. Blood and 24h urine were collected to perform hematological and biochemical analysis. BP was measured by the tail-cuff method. Kidney tissue was collected to mRNA and protein expression assays and to characterize renal lesions. A dose-dependent increase in red blood cells count, hematocrit and hemoglobin levels was found with rHuEPO therapy, in rHuEPO200, rHuEPO400 and rHuEPO600 groups. Increased reticulocyte count was found in rHuEPO400 and rHuEPO600 groups. BP raised in all groups receiving rHuEPO. The rHuEPO200 and rHuEPO600 groups presented increased kidney protein levels of HIF2α, a reduction in kidney protein levels of eNOS, and the highest grade of vascular and tubular renal lesions. Our study showed that rHuEPO-induced hypertension is present before significant hematological changes occur and, therefore, might involve direct (renal) and indirect (hematological) effects, which varies according to the dose used. The presence of renal hypoxia reduces eNOS activity. Excessive erythrocytosis increases blood hyperviscosity, which can be modulated by an increase in reticulocytes. Hypertension leads to early renal damage without alterations in traditional markers of renal function, thus underestimating the serious adverse effects and risks.